Response of human alveolar bone-derived cells to a novel poly(vinylidene fluoride-trifluoroethylene)/barium titanate membrane - Teixeira, L. N.; Crippa, G. E.; Gimenes, R. [UNESP]; Zaghete, M. A. [UNESP]; Oliveira, P. T. de; Rosa, A. L.; Beloti, M. M. (Springer, 2011)
This study investigated the response of human alveolar bone-derived cells to a novel poly(vinylidene fluoride-trifluoroethylene)/barium titanate (P(VDF-TrFE)/BT) membrane. Osteoblastic cells were cultured in osteogenic conditions either on P(VDF-TrFE)/BT or polytetrafluoroethylene (PTFE) for up to 14 days. At 7 and 14 days, the mRNA expression of Runt-related transcription factor 2 (RUNX2), Type I collagen (COL I), Osteopontin (OPN), Alkaline phosphatase (ALP), Bone sialoprotein (BSP), and Osteocalcin (OC), key markers of the osteoblastic phenotype, and of Bcl2-associated X protein (Bax), B-cell CLL/lymphoma 2 (Bcl-2), and Survivin (SUR), associated with the control of the apoptotic cell death, was assayed by real-time PCR. In situ ALP activity was qualitatively evaluated by means of Fast red staining. Surface characterization was also qualitatively and quantitatively assayed in terms of topography, roughness, and wettability. Cells grown on P(VDF-TrFE)/BT exhibited a significantly higher mRNA expression for all markers compared to the ones on PTFE, except for Bcl-2, which was not detected for both groups. Additionally, Fast red staining was noticeably stronger in cultures on P(VDF-TrFE)/BT at 7 and 14 days. At micron-and submicron scale, SEM images and roughness analysis revealed that PTFE and P(VDF-TrFE)/BT exhibited a smooth topography and a similar roughness, respectively. PTFE membrane displayed higher contact angles compared with P(VDF-TrFE)/BT, as indicated by wettability assay. The novel P(VDF-TrFE)/BT membrane supports the acquisition of the osteoblastic phenotype in vitro, while up-regulating the expression of apoptotic markers. Further in vivo experiments should be carried out to confirm the capacity of P(VDF-TrFE)/BT membrane in promoting bone formation in guided bone regeneration.